The Effect of Legal and Political on the Development of foreign Investment in Indonesia - Pramono, Budi; Larasati, Ayu (Journal Research of Social Science, Economics, and Management, 2022)
Indonesia is a country that is rich in natural potential and is the target of the world market. As a developing country with abundant natural resources that can use a source of funds to advance its economy, it is in dire need of assistance from foreign investors, both in terms of funding and management technology. Indonesia must create a comfortable climate for foreign investors in attracting foreign investors. Because these foreign investors are pretty sensitive to legal and political stability issues and do not want to take risks, the government needs to make policies that make them willing and comfortable to invest their capital. In making these policies, it is inseparable from political members who sit in the state legislature. These legal policies must be able to accommodate the needs of the state for the welfare of its citizens and, on the one hand, must also be able to provide leniency for these foreign investors. Law and politics here very closely relate to influencing the arrival of foreign investors. Politics that have a position more independent from the law will determine the direction of policies and legal products taken. Law acts as a product of current politics.